Determinan Keteraturan Kunjungan Masa Nifas di Puskesmas Topore Kabupaten Mamuju - Ashari, Agus Erwin; Nurdiana, Nurdiana (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2020)
The Maternal Mortality Rate in Indonesia according to SUPAS in 2015 is 305 per 100,000 live births. The number of maternal deaths in Mamuju District in 2015 was 12 people or 218 per 100,000 live births. The coverage of postpartum visits (KF3) in West Sulawesi Province tended to decline from 2012 to 2017. Post-natal visits in Mamuju District were 78.02% and in 2016 84.5%. The research objective was to determine the determinants that affect the regularity of postpartum visits. This study used a descriptive analytic design with a cross sectional approach. The sample in this study were postpartum mothers whose postpartum period had been completed and had a KIA book in the work area of ​​Puskesmas Topore from March to October 2018, namely 45 postpartum mothers who were selected by simple random sampling. The results showed that statistically there was no relationship between education and regular postpartum visits (p = 0.613). There was no relationship between work and regularity of postpartum visits (p = 0.063), there was no relationship between parity and regularity of postpartum visits (p = 0.481).